Bioactive peptides in the management of lifestyle-related diseases: Current trends and future perspectives. Issue 17 (25th September 2022) - Singh, Brij Pal; Aluko, Rotimi E.; Hati, Subrota; Solanki, Divyang
Abstract: Lifestyle-related diseases constitute a major concern in the twenty-first century, with millions dying worldwide each year due to chosen lifestyles and associated complications such as obesity, type 2 diabetes, hypertension, and hypercholesterolemia. Although synthetic drugs have been shown to be quite effective in the treatment of these conditions, safety of these compounds remains a concern. Natural alternatives to drugs include food-derived peptides are now being explored for the prevention and treatment of lifestyle-related complications. Peptides are fragments nascent in the primary protein sequences and could impart health benefits beyond basic nutritional advantages. Evidence suggests that by controlling adipocyte differentiation and lipase activities, bioactive peptides may be able to prevent obesity. Bioactive peptides act as agents against type 2 diabetes because of their ability to inhibit enzymatic activities of DPP-IV, α-amylase, and α-glucosidase. Moreover, bioactive peptides can act as competitive inhibitors of angiotensin-converting enzyme, thus eliciting an antihypertensive effect. Bioactive peptides may have a hypocholesterolemic effect by inhibiting cholesterol metabolism pathways and cholesterol synthesis. This review addresses current knowledge of the impact of food-derived bioactive peptides on lifestyle diseases. In addition, future insights on the clinical trials, allergenicity, cytotoxicity, gastrointestinal stability, and regulatory approvals have also been considered.